Nutritional status of adolescent pregnant women and newborn and consumption of food and nutrients - Falen, Juan (2015)
Pregnancy induces physiological and morphological changes in women and increases nutrients needs specially in adolescents, due to competence between ó growing mother and her developing fetus. This is a study done in 114 pregnant adolescents 28 at delivery and 96 at different gestational ages Results show a low calory intake, proteins 80% adequate and iron ingestion within recommended levels, but mainly non heminic. Anemia was prevalent in 62,5% and their babies weighed less than those of the general population, Serum iron was higher in newborns than in their mothers, but within low nor mal limits (normal values > 60 mg/dL) showing fetal nutritional dependence and competence of nutrient, between mother and fetus. An Integral Attention Adolescent Program would watch complementary nutrition, anemia, and avoidance of low birth-weight.